2019
DOI: 10.3847/2041-8213/ab212f
|View full text |Cite
|
Sign up to set email alerts
|

The First Bird’s-eye View of a Gravitationally Unstable Accretion Disk in High-mass Star Formation

Abstract: We report on the first bird's-eye view of the innermost accretion disk around the high-mass protostellar object G353.273+0.641, taken by Atacama Large Millimter/submillimeter Array long-baselines. The disk traced by dust continuum emission has a radius of 250 au, surrounded by the infalling rotating envelope traced by thermal CH 3 OH lines. This disk radius is consistent with the centrifugal radius estimated from the specific angular momentum in the envelope. The lower-limit envelope mass is ∼5-7 M ⊙ and accre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…They did not report the presence of a large (R > 1000 au) disc. Additional, spatially resolved compact discs have also been reported in recent literature (Fernández-López et al 2016;Motogi et al 2019). Multi-dimensional numerical simulations have also investigated disc formation and evolution in massive dense core collapse, either in the hydrodynamical case (e.g.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…They did not report the presence of a large (R > 1000 au) disc. Additional, spatially resolved compact discs have also been reported in recent literature (Fernández-López et al 2016;Motogi et al 2019). Multi-dimensional numerical simulations have also investigated disc formation and evolution in massive dense core collapse, either in the hydrodynamical case (e.g.…”
Section: Introductionmentioning
confidence: 64%
“…More recently, Motogi et al (2019) reported ALMA observation of a young high-mass protostellar object (10 M , no ultra-compact HII region), accreting at about 10 −3 M yr −1 , of which the characteristics are very consistent with the early evolutionary scenario of a low-mass protostar. From dust continuum emission, they report a disc mass of 2−7 M and a disc size of 250 au, which is associated with a lower limit of 0.4 for the Toomre parameter.…”
Section: Comparison With Observationsmentioning
confidence: 76%
“…This publication is based on the SEDIGISM and PPMAP data. models for HMSF have been discussed widely: (1) monolithic collapse (McKee & Tan 2003;Krumholz et al 2009;Csengeri et al 2018;Sanna et al 2019;Motogi et al 2019) and (2) competitive accretion Cyganowski et al 2017;Fontani et al 2018). It is possible that these models are not strongly and mutually incompatible as described by many current studies; these two models of HMSF are expected to be merged into a unified and consistent star formation model with the progress of observations and theories (Schilke 2015).…”
Section: Introductionmentioning
confidence: 91%
“…In the sub-millimetre, millimetre, and radio regimes, we can analyse the molecules forming further away in the disc Based on observations collected at the European Southern Observatory Paranal, Chile, Programme ID 0101.C-0317(A) and 098.C-0636(A). and dust continuum (Cesaroni et al 2005(Cesaroni et al , 2006(Cesaroni et al , 2007Motogi et al 2019). However, if we want to probe the inner gaseous disc within a few astronomical units from the central source, namely where accretion and ejection take place, we need to observe in the near-infrared (NIR).…”
Section: Introductionmentioning
confidence: 99%